Effect of calcium to silicon ratio on the microstructure of hydrated calcium silicate gels prepared under medium alkalinity - Hitch, Michael; Ba, Haojing; Li, Jiajie; Ni, Wen; Li, Ying; Ju, Yongjian; Zhao, Ben; Wen, Guoping (Elsevier, 2023)
The hydration of solid waste cementitious materials has a medium alkalinity and low calcium-to-silicate ratio (Ca/Si). Understanding how the hydration products behave in such a system is very important to optimize and create new solid waste cementitious materials. This paper investigates the effect of Ca/Si on the generated C–S–H gels under medium alkalinity. C–S–H gels were prepared by the double decomposition method at room temperature, and XRD, SEM, TG-DSC, XPS, and NMR examined the microstructure of C–S–H gels. Results show that the Cl- concentration in the solution controlled its pH, ranging between 11.1 and 12.8. However, the Ca/Si of C-S-H gels increased with the initial Ca/Si in solution. However, it couldn’t increase higher than 0.8 when the C–S–H was synthesized at a pH of about 12. With the increase in Ca/Si, the agglomeration of C–S–H gels increased, and the C–S–H became crystallized, the temperature of β -wollastonite formation enhanced. However, the β -wollastonite formation temperature of C–S–H gel synthesized under medium alkalinity was lower than that under high alkalinity. The increase in the Ca/Si of C–S–H gel decreased the Q3 type tetrahedra formation and increased the Q2 type tetrahedra formation. The variation of H2O/Si is related to the amount of Q2 and Q3 type tetrahedra in the C–S–H gel, which is determined by the synthesis method. Medium alkalinity could assist in generating C–S–H gel with low Ca/Si and high MCL. The results of this study could guide new solid wasted-based contentious materials production.